2016
DOI: 10.20960/nh.313
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of beverage consumption in adult populations from three different countries: do the international reference values allow establishing the adequacy of water and beverage intakes?

Abstract: Introduction: Recommendations of adequate total water intake (aTWI) have been proposed by the European Food Safety Agency (EFSA) and the Institute of Medicine (IOM) of the United States of America. However, there are differences in the approach used to support them: IOM recommendation is based on average intakes observed in NHANES III (Third National Health and Nutrition Examination Survey) and EFSA recommendation on a combination of observed intakes from 13 different European countries. Despite these recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Fluids and food are also an integral part of diet due to their nutrient and energy content. In particular, data from large population surveys in Spain, Mexico, and the United States revealed that mean energy intakes from foods and beverages ranged from 1,816 to 2,437 kcal with fluids contributing 12% (in Spain) to 21.7% (in Mexico) of total energy intake [19]. Dietitians are particularly concerned about the increased intakes of sugar-sweetened beverages (SSB) due to their detrimental consequences on oral health and body weight in children [20] and adults [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluids and food are also an integral part of diet due to their nutrient and energy content. In particular, data from large population surveys in Spain, Mexico, and the United States revealed that mean energy intakes from foods and beverages ranged from 1,816 to 2,437 kcal with fluids contributing 12% (in Spain) to 21.7% (in Mexico) of total energy intake [19]. Dietitians are particularly concerned about the increased intakes of sugar-sweetened beverages (SSB) due to their detrimental consequences on oral health and body weight in children [20] and adults [21].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from large cross-sectional surveys across Europe found that juices and SSB contributed 35-45% of TFI in children and adolescents and 15-20% in adults [3]. In the United States, data from the national survey showed that SSB intake contributed 6% of total caloric intake [19]. Drinking water instead of SSB is recommended by health organizations, as water is free of calories [1], while an increased water intake has been associated with higher diet quality [23].…”
Section: Introductionmentioning
confidence: 99%